Resectable extra-pleural and extra-meningeal solitary fibrous tumours: A multi-centre prognostic study. Issue 7 (July 2016) - Pasquali, S.; Gronchi, A.; Strauss, D.; Bonvalot, S.; Jeys, L.; Stacchiotti, S.; Hayes, A.; Honore, C.; Collini, P.; Renne, S.L.; Alexander, N.; Grimer, R.J.; et al.
Abstract: Background: Extra-pleural and extra-meningeal solitary fibrous tumour (SFT) is a rare sarcoma histotype curable with surgery in the majority of patients. The behaviour of these tumours ranges from indolent/very low grade to malignant/high grade but it is still not possible to accurately predict prognosis after surgery. We have investigated a multi-centre series to stratify the risk of recurrence to patients with SFTs. Methods: We retrospectively analysed the data from 243 patients who underwent surgery (2002–2011) at four sarcoma referral centres. Results: Upon univariate analysis, hypercellularity, atypia, necrosis, high mitotic rate (ie >4 mitoses/10 HPF) were associated with both disease-free and overall survival. Surgical margins were a significant prognostic factor for disease-free (P = 0.007) but not for overall survival. Unexpectedly, larger tumour size was associated with a better prognosis (P = 0.038) and fewer recurrences (P = 0.024). Upon multivariable analysis, high mitotic rate (hazard ratio, HR = 2.85, P = 0.002), cellular atypia (HR = 1.62, P = 0.015) and hypercellularity (HR = 1.82, P = 0.031) were significantly associated with recurrences. A SFT recurrence score has been provided to stratify risk of recurrence. Conclusion: This study provides a prognostic model to stratify risk of recurrence in patients with resectable SFTs. This allows clinician to decide on an optimal follow-up strategy and to select patients that may benefit from adjuvant treatments.